Reception study: The omission of narrative text in the English translation of Mo Yan's Life and Death Are Wearing Me Out - Guo, Jiahao; Zou, Deyan (Frontiers in Communication, 2023)
Reception Study: The Omission of Narrative Texts in the English Translation of Mo Yan’s Life and Death Are Wearing Me Out